Comparing Reading Comprehension Competence through Reading Aloud and Silent Reading among Indonesian EFL Learners in Senior High School - Aisiah, Iis Nur; Mahaputri, Ratna Andhika (Universitas Swadaya Gunung Jati, 2019)
Reading skill has its own modes; two of them are reading aloud and silent reading. Reading aloud and silent reading modes are interrelated with each other and affecting students' reading comprehension competence. The most EFL students’ common problems in the school is they do not know the appropriate techniques or modes applied in reading comprehension, therefore their reading comprehension results cannot be maximized. The researcher used quantitative research method and comparative study research design in conducting the research process. By using Reading Comprehension Test and interview, researcher collecting all the data in order to find deep information about how Indonesian EFL learners’ reading comprehension are through silent reading and reading aloud, its significance, and the factors that influence students’ reading comprehension score. The researcher took the samples in 34 students who divided into two groups; 17 students for silent group and 17 students for aloud group. The findings of this quantitative research indicated that there is no significance difference between reading aloud and silent reading regarding to Indonesian EFL learners reading comprehension competence and Reading Comprehension Factor (RCF) as the most factor that influence students’ reading comprehension score in silent group, while Reading Factor other than Comprehension (RFOC) as the most factor that influence students’ reading comprehension score in aloud group.